Academic Senate Minutes 2015-09-03 - Academic Senate:::::::::
Chair Report. Agenda approved. Minutes of 5/14/15 approved. Consent item: Faculty Eligible for Emeritus Status – Approved. Information items: End of Year Reports – Senate and Student Affairs Committee (emailed). Crash Course in Robert's Rules. President Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Associated Students Report. Orientation to Faculty Governance. EPC Report. FSAC Report. SAC Report. CFA Report. Staff Rep Report. Need for a Senate Resolution on Academic Integration and Appropriate University Support for the Green Music Center and its Programs, Series, Events, and Facilities. Group Photo